Cytotoxicity mechanisms of nitrogen-doped graphene obtained by electrochemical exfoliation of graphite rods, on human endothelial and colon cancer cells. (March 2020) - Baldea, Ioana; Olteanu, Diana; Filip, Gabriela Adriana; Pogacean, Florina; Coros, Maria; Suciu, Maria; Tripon, Septimiu Cassian; Cenariu, Mihai; Magerusan, Lidia; Stefan-van Staden, Raluca-Ioana; Pruneanu, Stela
Abstract: Three nitrogen-doped graphene samples were synthesized by electrochemical exfoliation of graphite rods via pulses of current. Depending on the synthesis conditions, the samples had different content of nitrogen (0.79, 2.56 and 2.33 wt%) and were denoted as NGr-1, NGr-2 and NGr-3, respectively. All samples consist in a mixture of graphene oxide, few- and multi-layer graphene. Several biological effects (cytotoxicity, oxidative stress induction, apoptosis, autophagy and DNA lesions) induced by the N-doped graphenes on human endothelial and colon cancer cells were investigated. The in vitro effects of graphenes were different and depended on the type of cell and the amount of nitrogen in the structure. On human endothelial cells, the graphenes showed antioxidant effects and were less toxic than on colon cancer cells, especially the one with low content of nitrogen (NGr-1). In contrast, on colon cancer cells the graphenes induced cell death by various mechanisms: free radicals generation, apoptosis, autophagy and DNA damage. The most severe DNA lesions and ultrastructural changes were produced by graphene with high content of nitrogen (NGr-2 and NGr-3). Our research demonstrates the cytotoxic effect of graphene with high content of nitrogen on colon cancer cells and antioxidant and protective properties on human endothelial cells. Graphical abstract: Image 1